Management of adults with primary frozen shoulder in secondary care (UK FROST): a multicentre, pragmatic, three-arm, superiority randomised clinical trial. Issue 10256 (3rd October 2020) - Rangan, Amar; Brealey, Stephen D; Keding, Ada; Corbacho, Belen; Northgraves, Matthew; Kottam, Lucksy; Goodchild, Lorna; Srikesavan, Cynthia; Rex, Saleema; Charalambous, Charalambos P; Hanchard, Nigel; Armstrong, Alison; et al.
Summary: Background: Manipulation under anaesthesia and arthroscopic capsular release are costly and invasive treatments for frozen shoulder, but their effectiveness remains uncertain. We compared these two surgical interventions with early structured physiotherapy plus steroid injection. Methods: In this multicentre, pragmatic, three-arm, superiority randomised trial, patients referred to secondary care for treatment of primary frozen shoulder were recruited from 35 hospital sites in the UK. Participants were adults (≥18 years) with unilateral frozen shoulder, characterised by restriction of passive external rotation (≥50%) in the affected shoulder. Participants were randomly assigned (2:2:1) to receive manipulation under anaesthesia, arthroscopic capsular release, or early structured physiotherapy. In manipulation under anaesthesia, the surgeon manipulated the affected shoulder to stretch and tear the tight capsule while the participant was under general anaesthesia, supplemented by a steroid injection. Arthroscopic capsular release, also done under general anaesthesia, involved surgically dividing the contracted anterior capsule in the rotator interval, followed by manipulation, with optional steroid injection. Both forms of surgery were followed by postprocedural physiotherapy. Early structured physiotherapy involved mobilisation techniques and a graduated home exercise programme supplemented by a steroid injection. Both early structured physiotherapy and postprocedural physiotherapy involved 12 sessions during up to 12 weeks. The primary outcome was the Oxford Shoulder Score (OSS; 0–48) at 12 months after randomisation, analysed by initial randomisation group. We sought a target difference of 5 OSS points between physiotherapy and either form of surgery, or 4 points between manipulation and capsular release. The trial registration is ISRCTN48804508. Findings: Between April 1, 2015, and Dec 31, 2017, we screened 914 patients, of whom 503 (55%) were randomly assigned. At 12 months, OSS data were available for 189 (94%) of 201 participants assigned to manipulation (mean estimate 38·3 points, 95% CI 36·9 to 39·7), 191 (94%) of 203 participants assigned to capsular release (40·3 points, 38·9 to 41·7), and 93 (94%) of 99 participants assigned to physiotherapy (37·2 points, 35·3 to 39·2). The mean group differences were 2·01 points (0·10 to 3·91) between the capsular release and manipulation groups, 3·06 points (0·71 to 5·41) between capsular release and physiotherapy, and 1·05 points (–1·28 to 3·39) between manipulation and physiotherapy. Eight serious adverse events were reported with capsular release and two with manipulation. At a willingness-to-pay threshold of £20 000 per quality-adjusted life-year, manipulation under anaesthesia had the highest probability of being cost-effective (0·8632, compared with 0·1366 for physiotherapy and 0·0002 for capsular release). Interpretation: All mean differences on the assessment of shoulder pain and function (OSS) at the primary endpoint of 12 months were less than the target differences. Therefore, none of the three interventions were clinically superior. Arthoscopic capsular release carried higher risks, and manipulation under anaesthesia was the most cost-effective. Funding: The National Institute for Health Research Health Technology Assessment programme.